1954
DOI: 10.1002/ange.19540662203
|View full text |Cite
|
Sign up to set email alerts
|

Physikalisch‐chemische Eigenschaften des Fluors

Abstract: Die Lithium-Verbindungen sind ungefahr ebenso reaktionsftihig wie die Magnesium-Verbindungen. Von besonderem lnteresse ist die Tatsache, daR sie bei der Uberfiihrung in Silicium-Verbindungen sehr vie1 bessere Ausbeuten liefern:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1957
1957
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…at very low salt activity ≈0.1 below the πtransition, then Figure 5a illustrates how the pull off-force is lowered by lowering pH. A possible explanation for this pH-induced decrease could be due to trapping of an excess of hydronium including hydration water in form of H9O4 + Eigen complexes at the collapsed EDL interface [45]. A trivial consequence of this gradual decrease in pull-off force is that the magnitude of the π-transition must be smaller at lower pH.…”
Section: Energy Required Inducing Fttsmentioning
confidence: 96%
“…at very low salt activity ≈0.1 below the πtransition, then Figure 5a illustrates how the pull off-force is lowered by lowering pH. A possible explanation for this pH-induced decrease could be due to trapping of an excess of hydronium including hydration water in form of H9O4 + Eigen complexes at the collapsed EDL interface [45]. A trivial consequence of this gradual decrease in pull-off force is that the magnitude of the π-transition must be smaller at lower pH.…”
Section: Energy Required Inducing Fttsmentioning
confidence: 96%
“…From the half-normal plot, it is observed that the temperature of the gas diffusion plate (T GDP ) is shown to have a very marginal effect on the etch rate. A relatively lower dissociation rate of F 2 is reported by Steudel et al (degree of dissociation, α ≈ 4%) at 1000 K [13], and (α < 1%) by Wicke et al at 600 K [14]. The above reported measurements are performed at the chamber pressure of around 1 bar.…”
Section: Analysis Of Etch Rate As the Dependent Variablementioning
confidence: 72%